KOLABORASI ANTAR STAKEHOLDERS PENTA HELIX DALAM PENGEMBANGAN KOTA KREATIF (Studi di Kota Malang) - Rozikin, M.AP., Dr. Mochamad (Badan Perencanaan Pembangunan Kota Malang, 2019)
Creative city is a city that in its development relies on aspects of human creativity. Creative cities are also inseparable from creative economy. The creative economy in Malang City is classified into 16 subsectors. The development of creative cities must be done collaboratively stakeholders. Stakeholders in the creative city are known as penta helix. Penta helix consists of Academicians, Business, Community, Government and Media (ABCGM). This study uses the theory of the collaboration process from Ansell and Gash, the collaboration of Emerson, Nabatchi and the theory of penta helix. This research uses descriptive qualitative type with three focuses, namely the process of collaboration, the role of actors in penta helix and the results of collaboration. The results of the study show that the collaboration process in Malang City has gone quite well. The positive collaboration result is the roadmap policy making that begins the construction of the MCC building. While the negative results in question are individuals involved in collaboration experiencing saturation due to intensive meetings.